Relationships between landform properties and vegetation patterns in the Cerro Zonda Mt., Central Precordillera of San Juan. Argentina. (December 2019) - Flores, Daniel; Ocaña, Emmanuel; Rodríguez, Aixa Inés
Abstract: Arid environments are dynamic systems due, in part, to the action of hydrological processes. However, studies on the relationship between the abiotic factors and the properties of arid vegetation communities of Argentina are scarce. In this paper, the connection between these two parameters is researched using DEM analysis and exhaustive field work in order to model vegetation changes and landform evolution. The aim of this paper is to determine whether geomorphological properties influence vegetation patterns along the Cerro Zonda Mt. This mountain range is located in an arid central sector of Monte Desert, a phytogeographic region of Argentina. The classification of geomorphological units was made by combining interpretation of images provided by Google Earth and the analysis of Alos Palsar DEM using SAGA GIS. The geomorphic units were sorted into categories based on slope, elevation, hillslope aspect, terrain roughness and topographic wetness. In addition, surface characteristics of units were evaluated considering the properties of coverage of rock fragments, fine sediment and mulch. Afterwards, community patterns were explored using PCA analysis and linear correlations. Our results showed five geomorphological units: a) Pediment of mountain upland; b) Active landforms; c) Inactive landforms; d) Inactive landforms raised by neotectonics and e) Lacustrine landforms. The vascular flora is represented by 35 species distributed in 15 families. The landforms' surface property of rock fragments is correlated both directly with species richness and inversely with vegetation coverage. Furthermore, roughness explains the higher vegetation diversity while slope promotes an increase in the vegetation cover, but this does not suggest more species richness. In addition, our results indicate that topographic wetness, as well as hillslope aspect and elevation, are not determining variables of vegetation patterns across the landforms. The vegetation patterns of Cerro Zonda Mt. are associated with topographic properties as slope and roughness. In turn, rock fragment surface coverage also affects these vegetation patterns. The landforms' properties not only expose spatial changes in the development of the plant communities but also show the direct implications of geomorphological changes over such communities. In particular, there is a need to integrate a geomorphological view for the analysis of vegetation in arid zones. Highlights: The geotechnical characteristics of landforms are a key element in the classification process. The vegetation of all five landform types was represented graphically along a toposequence. Slope values and roughness determine the vegetation coverage at a regional scale. The high coverage of rock fragments contributes to the formation of new areas due to the retainment of fine sediments.